Analysis of the health effects of multiple social networks on the older adult: the substitution role of labor participation - Zhiying Li (Frontiers Media S.A., 2024)
ObjectivesThis study aims to examine the role of social networks in influencing the physical and mental health of older Chinese adults, investigating both the underlying mechanisms and the associations between social networks, labor force participation, and health outcomes.MethodsUsing data from the 2021 China General Social Survey (CGSS), we analyzed a sample of 1,332 older adults, incorporating demographic and health-related variables. Ordinary least squares (OLS) regression and mediation analysis were conducted to evaluate the effects of social networks on health outcomes, with subgroup analyses by gender and education level. Stata 18.0 and SPSS were employed to perform all statistical analyses.ResultsSocial networks demonstrate a significant positive effect on overall, physical, and mental health at the 1% level, with weak-tie networks exhibiting a more substantial impact on health (β = 0.1146, p < 0.01). In promoting physical health, social networks have a coefficient of 0.1371 (p < 0.001) for females and 0.2128 (p < 0.001) for males. Among individuals with lower education, the coefficient is 0.1561 (p < 0.001), while for those with higher education, it is 0.2184 (p < 0.001). Regarding mental health, social networks yield a coefficient of 0.0747 (p > 0.05) for females and 0.1095 (p < 0.01) for males; for individuals with lower education, the coefficient is 0.0914 (p < 0.01), and for those with higher education, it is 0.0441 (p > 0.05). Media use, subjective wellbeing, and perceived social class are key explanatory mechanisms in the relationship between social networks and health of the older adult. Notably, subjective wellbeing and perceived social class function as chain mediators between social networks and health outcomes. The interaction between social networks and labor participation reveals a significant negative coefficient (β = −0.1864, p < 0.01).ConclusionSocial networks contribute to improved health in older adults, with weak ties playing a particularly significant role, although the effect varies across subgroups. Media use, subjective social class, and wellbeing are important mechanisms linking social networks with older adult health, while labor force participation may serve as a substitute for social networks in health promotion among older adults. This study will inform the improvement of older adults health and the development of labor policies for older adults.